On the application of Fubini’s theorem in the integration of functiions of two variables in a measure space - Akinremi, 'Bankole V; Idiong, Ubong Sam; Akintewe, Bridjet; Famuagun, Kayode Samuel (International Journal of Advanced Mathematical Sciences, 2013)
We consider the integration of functions of two variables in a measure space. Some definitions, theorems and proves relating to measurable functions and measure space were considered by using Fubini's theorem. Application on the improvement of the Jensen's inequality with respect to the probability measure space is treated.